Human epidermal growth factor receptor 2 expression in gynecologic serous carcinomas and preliminary analysis of its characteristics in patients post-neoadjuvant chemotherapy - Liu, Lili; Cheng, Naixuan; Kong, Fangzhou; Shen, Danhua (Frontiers in Oncology, 2026)
ObjectivesThis study aimed to investigate human epidermal growth factor receptor 2 (HER2) protein expression and gene amplification status in uterine serous carcinoma (USC) and ovarian high-grade serous carcinoma (HGSC), determine the frequencies of HER2 overexpression/amplification and HER2-low expression, evaluate two current HER2 interpretation criteria, and analyze the relationship between HER2 status and patient prognosis.MethodsA total of 51 patients with USC (including eight cases of mixed endometrial adenocarcinoma with predominant serous carcinoma components) and 165 patients with ovarian HGSC (including 43 patients who received neoadjuvant chemotherapy) were retrospectively recruited from the Department of Pathology, Peking University People’s Hospital between January 2019 and January 2025. Clinical and pathological characteristics were summarized. HER2 protein expression in whole-tissue sections was assessed using immunohistochemistry (IHC). HER2 scoring was performed according to two criteria: the 2023 American Society of Clinical Oncology/College of American Pathologists HER2 Testing Guidelines in Breast Cancer and the HER2 Immunohistochemistry Scoring System for Endometrial Serous Carcinoma proposed by the International Society of Gynecological Pathologists (ISGyP). Fluorescence in situ hybridization (FISH) was subsequently performed on cases with IHC scores of 1+, 2+, or 3+ for validation. Survival analysis was conducted based on HER2 status.ResultsHER2 gene amplification was detected in 15/51 (29.4%) tissues from patients with USC (including mixed carcinomas with predominant serous morphology). HER2 amplification was identified in 6/122 (4.9%) tissues from patients with primary ovarian HGSC without prior chemotherapy, and in 3/43 (7.0%) tissues from patients with ovarian HGSC with residual disease after neoadjuvant chemotherapy. Evaluation of HER2 IHC results using both interpretation criteria revealed no difference in HER2 3+ expression rates for both USC and ovarian HGSC. However, differences existed in the classification of HER2-low expression (defined as IHC 2+ with negative FISH or IHC 1+). The ISGyP criteria identified more cases with low HER2 expression. For patients with USC, HER2 positivity was not statistically significantly associated with overall survival (OS) or progression-free survival (PFS), although it showed a trend toward higher recurrence. In terms of prognosis, for patients with ovarian HGSC group, HER2 positivity was associated with worse OS (p = 0.049). Among patients with ovarian HGSC after neoadjuvant chemotherapy, HER2 positivity was a strong predictor for shorter PFS (p = 0.003).ConclusionA certain proportion of USC and ovarian HGSC cases exhibit HER2 positivity and HER2-low expression. Different interpretation criteria lead to variations in the assessment of HER2 IHC results. The ISGyP criteria can identify more cases with low HER2 expression. Moreover, our findings suggest that HER2 status could be a relevant prognostic marker in these malignancies. Traditional anti-HER2 targeted therapies are indicated for HER2-positive patients, while a broader population of patients with HER2-low expression may benefit from novel anti-HER2 antibody-drug conjugates.